Tax-benefit revealed social preferences - François Bourguignon; Amedeo Spadaro (University of Essex, Institute for Social and Economic Research (ISER), 2008)
This paper inverts the usual logic of applied optimal income taxation. It starts from the observed distribution of income before and after redistribution and corresponding marginal tax rates. Under a set of simplifying assumptions, it is then possible to recover the social welfare function that would make the observed marginal tax rate schedule optimal. In this framework, the issue of the optimality of an existing tax-benefit system is transformed into the issue of the shape of the social welfare function associated with that system and whether it satisfies elementary properties. This method is applied to the French redistribution system with the interesting implication that the French redistribution authority may appear, under some plausible scenario concerning the size of the labor supply behavioral reactions, non Paretian (e.g. giving negative marginal social weights to the richest class of tax payers).
Keywords: H11; H21; D63; C63; 330; Social Welfare Function; Optimal Income Tax; Microsimulation; Optimal Inverse Problem; Einkommensverteilung; Steuerbegünstigung; Sozialpolitik; Soziale Wohlfahrtsfunktion; Frankreich